Gastric Helicobacter Spp. Infection in Captive Neotropical Brazilian Feline - Luiz de Camargo, Pedro (Sociedade Brasileira de Microbiologia, 2011)
Ten captive neotropical Brazilian feline were submitted to gastroscopic examination and samples of gastric mucosa from fundus, corpus and pyloric antrum were evaluated for the presence of Helicobacter species. Warthin-Starry (WS) staining and PCR assay with species-specific primers and enzymatic cleavage were applied for bacterial detection and identification. Histological lesions were evaluated by haematoxylin and eosin staining. All animals showed normal gross aspect of gastric mucosa. Helicobacter heilmannii was confirmed in 100% of the samples by WS and PCR assay. Mild lymphocytic infiltrate in the lamina propria was observed in eight animals, mainly in the fundus region. Small lymphoid follicles were seen in three animals. No significant association between Helicobacter infection and histological findings was verified. These observations suggest that gastric Helicobacter spp. could be a commensal or a eventual pathogen to captive neotropical feline, and that procedures, way life, and stress level on the shelter apparently had no negative repercussion over the integrity of the stomach.